An empirical research on Hofstede’s cultural dimensions on perceived job satisfaction among expatriates of Scope International (M) Sdn. Bhd. / Muhammad Arif Kamarudzaman - Kamarudzaman, Muhammad Arif (Faculty of Business and Management, 2015)
This research was undertaken at Scope International (M) Sdn. Bhd, the wholly-owned subsidiary of Standard Chartered Bank, United Kingdom, on the topic of “An Empirical Research on Hofstede’s Culture Dimensions on Perceived Job Satisfaction among Expatriates of Scope International (M) Sdn. Bhd.”. Scope International is a growing company which employs many expatriates. The year 2014 however, had not been a good time for the company as there is a drop in sales and revenue as reported in the annual report of 2014. Apart from economic reasons, some recruiters from the human resources had explained that job satisfaction and cultural reasons among expatriates may be one of the symptoms for this drop in sales and revenue. The main purpose of this study is to research on the Hofstede’s cultural dimension on perceived job satisfaction of the expatriates. There are four dimensions that will be studied in this paper are power distance, uncertainty avoidance, individualism / collectivism and masculinity / femininity. Primary data were collected from a sample of 80 expatriates in Technology and Engineering departments, through distribution of questionnaires that are used for analysis. Only 72 questionnaires are returned, out of the 80 sample. The study revealed that the mentioned problem did not actually appear among the expatriates and have very high job satisfaction. Also there are significant relationship between the perceived job satisfaction and cultural dimension with power distance being the most influential. The researcher recommended that Talent Acquisition should conduct proper investigation on the claimed problems; conduct engagement session with the expatriates; empowers the Talent Acquisition skills and expertise; organise Human Resources open day more frequently; and maintain the already good cultural diversity and inclusion.